Upaya Pencegahan Gizi Buruk pada Masyarakat Marginal di Kota Makassar - Ahmad Syaekhu; Sri Handayani; Sitti Hardiyanti Arhas (Postgraduate, University of Mataram, 2023)
The Indonesian government has made efforts to improve nutrition through counseling and education through community health centers, but these efforts are considered to be less effective. The aspects to be looked at are community characteristics, initial knowledge and attitudes about eating habits and environmental sanitation, and educational models for preventing malnutrition that are currently needed. Respondents in this study were 80 people. The data that has been collected is analyzed to develop an educational model design. Data analysis was carried out using percentage analysis. Based on the results of data processing that has been carried out, it was found that the average mother in marginalized communities is a mother of productive age, the number of children in marginalized communities is on average 1-2 children, feeding habits are in a good category, mothers in the community Marginal people on average have moderate knowledge about nutrition, attitudes about children's health are quite good, sanitation is in good condition, and marginalized communities want education with home visits conducted once a month.